Relationship of Training, Competency, Adoption of Big Data Analytics With Audit Quality Survey at BPK RI - Vina Octaviana; Hamzah Ritchi; Zaldy Adrianto (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This research was conducted based on the phenomenon of BPK audit quality still needs to be improved when facing a lot of data with large capacity, variety, and high frequency in audit practice. One of the technological advances in facing these challenges is the emergence of big data analytics (BDA). The purpose of this study is to determine the effect of training, competence, and adoption of big data analytics on BPK audit quality. This research method is a quantitative method with a survey approach at the BPK RI office. This study uses primary data obtained through filling out an online questionnaire by 184 respondents who were sampled in the study. The data analysis method of this research is descriptive statistics and path analysis using the IBM SPSS Statistics 26 program. The results showed that training, competence, and adoption of big data analytics had a positive and significant effect on audit quality both partially and simultaneously.